Experimental infection with Leishmania (Viannia) braziliensis, and Leishmania (Leishmania) amazonensis in the marmoset, Callithrix penicillata (Primates: Callithricidae) - Cuba, César Augusto Cuba (1990)
Foureen marmosets (Callithrix penicillata) were inoculated intradermally with promastigotes and/or amastigotes of Leishmania (Viannia) brazilensis (L. (V) b.) strains MHOM/BR/83/LTB-300MHOM/BR/85/LTB-12 MHOM/BR/81/LTB-179 and MHOM/BR/82/LTB-250. The evolution of subsequent lesions was studied for 15 to 75 weeks post-inoculation (PI). All but of the L. (V) b. injected marmosets developed a cutaneous lesion at the point of inoculation after 3 to 9 weeks, characterized by the appearance of subcutaneous nodules containing parasites. parasites were isolated by culture (Difco Blood Agar) from all 11 positive animals. The maximum size of the lesions was variable and ranged between 37 mm² to 107 mm². Ulceration of primary nodules became evident after 3 to 12 weeks in all infected marmosets, but was faster and larger in 5 of the 11 animals. The active lesions persisted in 9 out of 11 Callithrix until the en of the observation period, which varied from 15-75 weeks. In 3 animals spontaneous healing of their lesions (13 to 25 weeks, PI) was observed buth with cryptic parasitism. In another 2 infected animals there was regression followed by reactivation of the cutaneous lesions. The appearance of smaller satellite lesions adjacent to primary ones, as well as metastatic lesions to the ear lobes, were documented in 2 animals. Promastigotes of L. (Leishmania) amazonensis (L.(L)a.) MHOM/BR/77/LTB-16 were inoculated in 1 marmoset. This animal remained chronically infected for 6 months and the lesions developed in a similar manner to L.(V)b. infected marmosets. No significant differences in clinical and parasitological behaviour were observed between promastigote or amastigote derived infections of the 2 species. Both produced chronic, long lasting lesions which eventually healed. The same was true for parameters of size and ulceration. Skin tests converted to parasite in 11 of 15 inected masmosets and in 10 of 12 parasite positive animnals. Moderate levels of circulating antibodies were also observed by IFAT /IgG assays. In spite of the failure to reproduce the mucosal form of the disease, an important aspect of the Callithrix model in experimental cutaneous leishmaniasis lies in the reproduction of 2 clinical events that are common in humans, namely, the chronic ulceration and spontaneous healing of the lesions.